Frederick Douglass prophet of freedom - Blight, David W. 1949- (Simon & Schuster Paperbacks, 2018)
"The definitive, dramatic biography of the most important African-American of the nineteenth century: Frederick Douglass, the escaped slave who became the greatest orator of his day and one of the leading abolitionists and writers of the era. As a young man Frederick Douglass (1818-1895) escaped from slavery in Baltimore, Maryland. He was fortunate to have been taught to read by his slave owner mistress, and he would go on to become one of the major literary figures of his time. He wrote three versions of his autobiography over the course of his lifetime and published his own newspaper. His very existence gave the lie to slave owners: with dignity and great intelligence he bore witness to the brutality of slavery. Initially mentored by William Lloyd Garrison, Douglass spoke widely, often to large crowds, using his own story to condemn slavery. He broke with Garrison to become a political abolitionist, a Republican, and eventually a Lincoln supporter.